Study of the Chemotactic Response of Multicellular Spheroids in a Microfluidic Device - Ayuso, Jose M.; Basheer, Haneen A.; Monge, Rosa; Sánchez-Álvarez, Pablo; Doblaré, Manuel; Shnyder, Steven D.; Vinader, Victoria; Afarinkia, Kamyar; Fernández, Luis J.; Ochoa, Ignacio (PloS one, 2015)
We report the first application of a microfluidic device to observe chemotactic migration in multicellular spheroids. A microfluidic device was designed comprising a central microchamber and two lateral channels through which reagents can be introduced. Multicellular spheroids were embedded in collagen and introduced to the microchamber. A gradient of fetal bovine serum (FBS) was established across the central chamber by addition of growth media containing serum into one of the lateral channels. We observe that spheroids of oral squamous carcinoma cells OSC-19 invade collectively in the direction of the gradient of FBS. This invasion is more directional and aggressive than that observed for individual cells in the same experimental setup. In contrast to spheroids of OSC-19, U87-MG multicellular spheroids migrate as individual cells. A study of the exposure of spheroids to the chemoattractant shows that the rate of diffusion into the spheroid is slow and thus, the chemoattractant wave engulfs the spheroid before diffusing through it.